Powering Artificial Enzymatic Cascades with Electrical Energy. Issue 27 (28th April 2020) - Al‐Shameri, Ammar; Petrich, Marie‐Christine; junge Puring, Kai; Apfel, Ulf‐Peter; Nestl, Bettina M.; Lauterbach, Lars
Abstract: We have developed a scalable platform that employs electrolysis for an in vitro synthetic enzymatic cascade in a continuous flow reactor. Both H2 and O2 were produced by electrolysis and transferred through a gas‐permeable membrane into the flow system. The membrane enabled the separation of the electrolyte from the biocatalysts in the flow system, where H2 and O2 served as electron mediators for the biocatalysts. We demonstrate the production of methylated N‐heterocycles from diamines with up to 99 % product formation as well as excellent regioselective labeling with stable isotopes. Our platform can be applied for a broad panel of oxidoreductases to exploit electrical energy for the synthesis of fine chemicals. Abstract : A bioelectrochemical flow system has been developed to power enzymatic cascades in vitro. H2 and O2 are generated by electrolysis and serve as electron mediators for oxidoreductases. Methylated N‐heterocycles were generated from diamines with up to 99 % product formation and a labeling regioselectivity of up to 99 %.